Independence corrupted : how America's judges make their decisions - Schudson, Charles B. (The University of Wisconsin Press, 2018)
"[The author] takes readers behind the bench to probe judicial minds analyzing actual trials and sentencings--of abortion protesters, murderers, sex predators, white supremacists, and others. He takes us into chambers to hear judges forging appellate decisions about life and death, multimillion-dollar damages, and priceless civil rights. And, most significantly, he exposes the financial, political, personal, and professional pressures that threaten judicial ethics and independence. As political attacks on judges increase, [the author] calls for reforms to protect judicial independence and for vigilance to ensure justice for all."--